Long-lasting effects of prenatal stress on HPA axis and inflammation: A systematic review and multilevel meta-analysis in rodent studies. (August 2021) - Creutzberg, Kerstin Camile; Sanson, Alice; Viola, Thiago Wendt; Marchisella, Francesca; Begni, Veronica; Grassi-Oliveira, Rodrigo; Riva, Marco Andrea
Highlights: We performed a meta-analysis to quantify the effects of PNS on HPA axis and inflammation. PNS exposure leads to a consistent dysfunction in the HPA axis. Peripheral CORT as well as central CRH and CRHR2 levels are altered by PNS. Exposure to PNS produces heterogeneous results on inflammatory markers. Abstract: Exposure to prenatal stress (PNS) can lead to long-lasting neurobiological and behavioral consequences for the offspring, which may enhance the susceptibility for mental disorders. The hypothalamus-pituitary-adrenal (HPA) axis and the immune system are two major factors involved in the stress response. Here, we performed a systematic review and meta-analysis of rodent studies that investigated the effects of PNS exposure on the HPA axis and inflammatory cytokines in adult offspring. Our analysis shows that animals exposed to PNS display a consistent increase in peripheral corticosterone (CORT) levels and central corticotrophin-releasing hormone (CRH), while decreased levels of its receptor 2 (CRHR2). Meta-regression revealed that sex and duration of PNS protocol are covariates that moderate these results. There was no significant effect of PNS in glucocorticoid receptor (GR), CRH receptor 1 (CRHR1), pro- and anti-inflammatory cytokines. Our findings suggest that PNS exposure elicits long-lasting effects on the HPA axis function, providing an important tool to investigate in preclinical settings key pathological aspects related to early-life stress exposure. Furthermore, researchers should be aware of the mixed outcomes of PNS on inflammatory markers in the adult brain.